2016
DOI: 10.3727/096504016x14618564639178
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of Long Noncoding RNA PCAT6 Inhibits Proliferation and Invasion in Lung Cancer Cells

Abstract: As a newly identified oncogenic long noncoding RNA (lncRNA), prostate cancer-associated transcript 6 (PCAT6) promoted cellular proliferation and colony formation of prostate cancer. However, the biological function of PCAT6 in lung cancer is still largely unknown. In this study, we found that PCAT6 is significantly increased in cancer tissues compared to normal tissues and positively correlates with metastasis of lung cancer in patients. We then examined PCAT6 expression in lung cancer cell lines and identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
70
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 46 publications
(20 reference statements)
2
70
1
Order By: Relevance
“…In Wan et al's study, PCAT6 was considered as a potential diagnostic and prognostic biomarker in non‐small cell lung cancer . PCAT6 may indirectly regulate c‐Myc and p53 expression in lung cancer which may contribute to the modulation of lung cancer cells proliferation and invasion . In the present study, we also observed higher PCAT6 expression in CRC tissues.…”
Section: Discussionmentioning
confidence: 97%
“…In Wan et al's study, PCAT6 was considered as a potential diagnostic and prognostic biomarker in non‐small cell lung cancer . PCAT6 may indirectly regulate c‐Myc and p53 expression in lung cancer which may contribute to the modulation of lung cancer cells proliferation and invasion . In the present study, we also observed higher PCAT6 expression in CRC tissues.…”
Section: Discussionmentioning
confidence: 97%
“…Increased SNHG3 expression is associated with malignant status and worse overall survival, recurrence-free survival and disease-free survival in hepatocellular carcinoma patients [50]. PCAT6 may play an oncogenic role in lung cancer progression, and it negatively correlates with the overall survival of lung cancer patients [51]. MIAT may promote the development of lung adenocarcinoma via the MIAT-miR-106-MAPK signalling pathway loop [52].…”
Section: Discussionmentioning
confidence: 99%
“…Long non‐coding RNAs (lncRNAs), transcripts longer than 200 nucleotides without protein translation, have been observed to function in carcinogenesis . Some can work as clinically relevant biomarkers since being linked to prognosis .…”
Section: Introductionmentioning
confidence: 99%